Assessment of musculoskeletal disorders among palm oil farmers with SNI 9011:2021 in Muara Wahau - Pawitra, Theresia Amelia; Fathimahhayati, Lina Dianati; Sitania, Farida Djumiati; Mas’ud, Mufid; Marhani, Marhani (Universitas Mercu Buana, 2023)
Indonesia is the world's largest producer of palm oil, with millions of hectares of plantations. However, along with the growth of the palm oil industry, various challenges and issues related to the worker welfare have emerged. One important issue is musculoskeletal disorders or health problems associated with work in palm oil plantations. Workers in palm oil plantations are often exposed to heavy and repetitive work conditions, such as carrying heavy loads, performing monotonous movements, and working in non-ergonomic positions. These factors can increase the risk of musculoskeletal disorders, such as back pain, shoulder pain, neck pain, and other health issues. Therefore, this research aims to evaluate existing musculoskeletal disorders and provide recommendations for improvement and management of ergonomic risks in PT. DSN in Muara Wahau. The research methods include direct observation of palm oil farmers during their work, structured interviews to gather information on complaints and ergonomic risks, and the use of ergonomic analysis methods in accordance with the SNI 9011:2021 standard. The data obtained will be analyzed to identify ergonomic risk factors contributing to musculoskeletal disorders. The results of this study showed that all of palm oil harvesting workers experienced high risk level on their neck, while all of palm oil transportation workers encountered high risk on their elbow. Stretching or warm-up exercises before and after work were recommended to reduce the risk of injuries caused by non-ergonomic work positions among harvesting workers. Furthermore, redesigning Hook-T was recommended in order to minimize the MSD among palm oil transportation workers.